(untitled) (Journal of Governance and Development (JGD), 2021)
This study examined the state of women political participation and representation in Africa and Asian continents. Relying on secondary data comprised of books and journal articles, descriptive qualitative design, and the liberal democratic theory as a framework of analysis, several results emerged. Emerged results showed positive increase in women political participation and representation in several government levels in both Africa and Asia, but not without challenges. It revealed some of the challenges working against women to include religion, cultural beliefs, male dominance, lack of family support and poor financial resources in both continents. Other include poor education, political violence, weak political institutions, stereotype, and insult from the menfolk. These are in sharp contrast to the teachings and principles of liberal democratic theory and democratic governance. In a democracy, every citizen including women have the right to participate, elect and be elected for public office which is the hallmark of democracy. In both continents, however, upward movement in women political participation and representation is evident, but they continue to suffer degrees of discrimination and marginalization from their menfolk and the political system. The above shows the need for political leaders to adhere to their constitution, teachings of liberal democracy, quota measures amongst other policies to remedy the predicament of women in public life. It would throw-up a better order, women would be represented, and democracy consolidated. There is a need to expand the research to other continents as it would be useful to women, policymakers, and researchers.